1. -1
2. 1/2
not sure:
3. 7? —> 7x 1/7x=7x1= 7
4. 1/11?
A function can be represented by equations and tables
- 4 users are logged in by 9am
- The domain is [3,23] and the range of the function is [3,4]
<h3>The number of users at 9am</h3>
The function is given as:
![g(x) = \frac14 \sqrt{x - 3} + 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%5Cfrac14%20%5Csqrt%7Bx%20-%203%7D%20%2B%203)
At 9am, x = 9.
So, we have:
![g(x) = \frac14 \sqrt{9 - 3} + 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%5Cfrac14%20%5Csqrt%7B9%20-%203%7D%20%2B%203)
![g(x) = \frac14 \sqrt{6} + 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%5Cfrac14%20%5Csqrt%7B6%7D%20%2B%203)
Simplify
![g(9) = 3.6](https://tex.z-dn.net/?f=g%289%29%20%3D%203.6)
Approximate
![g(9) = 4](https://tex.z-dn.net/?f=g%289%29%20%3D%204)
Hence, 4 users are logged in by 9am
<h3>The domain</h3>
Set the radical to 0
![x - 3 = 0](https://tex.z-dn.net/?f=x%20-%203%20%3D%200)
Solve for x
![x = 3](https://tex.z-dn.net/?f=x%20%3D%203)
The maximum time after midnight is 23 hours.
So, the domain is [3,23]
<h3>The range</h3>
When x = 3, we have:
![g(x) = \frac14 \sqrt{x - 3} + 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%5Cfrac14%20%5Csqrt%7Bx%20-%203%7D%20%2B%203)
![g(3) = \frac 14 * \sqrt{3 - 3} + 3 = 3](https://tex.z-dn.net/?f=g%283%29%20%3D%20%5Cfrac%2014%20%2A%20%5Csqrt%7B3%20-%203%7D%20%2B%203%20%3D%203)
When x = 23, we have:
![g(23) = \frac 14 * \sqrt{23 - 3} + 3 = 4](https://tex.z-dn.net/?f=g%2823%29%20%3D%20%5Cfrac%2014%20%2A%20%5Csqrt%7B23%20-%203%7D%20%2B%203%20%3D%204)
So, the range of the function is [3,4]
Read more about domain and range at:
brainly.com/question/2264373
Answer:
add and multiply
Step-by-step explanation:
add them up and get your answer
then multiply that answer by 5
Answer:
B
Step-by-step explanation:
No matter what value you multiply a, the fraction will remain unchanged. That is because you can divide an a out from the numerator and the denominator. Thus, doubling a has no affect on the fraction, and in fact, u can simplify it to just bc. Now, if you halve b, it will simply just halve the actual value. When you halve b, you are simply executing (1/2)(b)(c). Therefore, you can rearrange the expression to be (1/2)(bc), which is just halving bc. If you decrease by 1/2, it's the same thing as being half of the value it was before. Therefore, the answer is b.
Answer:
Step-by-step explanation: